Doživljanje stresa in izgorelosti, povezanih z delom z učenci s posebnimi potrebami pri učiteljih v osnovni šoli - Košir, Katja (Psihološka obzorja (Ljubljana), 2014)
The aim of the present study was to examine the predictive value of elementary school teachers' workplace characteristics on work stress and burnout. Workplace characteristics were defined as job demands and resources, which were further divided into general and specific, related to work with special education needs students. We examined whether variables related to work with special education needs students explained incremental variance in stress and burnout above and beyond general workplace characteristics. Elementary school teachers from all twelve regions of Slovenia (N ranges from 439 to 886) took part in the study. The results have shown that workplace characteristics independently predict a significant amount of variance in stress, emotional exhaustion and depersonalization among teachers. General job demands and specific demands related to special education needs students are the highest and most stable predictors of all three studied criteria. Based on our findings, we suggest several measures which can help to alleviate stress and foster efficient coping strategies.
Keywords: teachers; učitelji; elementary schools; osnovne šole; stres; stress; coping behavior; spoprijemanje; burnout; izgorelost; special education students; učenci s posebnimi potrebami